Socioeconomic Risk Factors for Asthma in Child (Medical Forum Monthly, 2024)
Aim and Objective: The purpose of the study was to explore and explain different socioeconomic conditions and factors related to childhood asthma. Design of Study: Cross sectional descriptive study. Place and Duration of Study: This study was conducted at the Children’s Hospital & the Institute of Child Health, Lahore for a period of three month. Patients and Methods: This is a descriptive study done at the asthma clinic of the Children’s Hospital & the Institute of Child Health, Lahore. Total 110 patients were included in the study between 2-16 years. An objectively designed structured questionnaire was used and data was collected after taking consent from the parents. Results: Out of 110 patients, the commonest age was 2-8 years for both males and females. The disease was most common in boys (63.6%) and urban area (57.3%) had higher frequency than patients from semi urban (24.5%) or rural areas (18.2%). Asthma was more common in lower and middle class than upper. Different socioeconomic risk factors involved in the increased frequency of asthma were smoking, animals at home and environmental dust. Allergic reactions to food, change in weather and preceding upper respiratory tract infections also play an important role. Conclusion: Poor socioeconomic class, uneducated families, urban life and environmental allergen exposure are responsible for increase frequency of asthma and by investing resources in to community based education and support services we can provide a better control of asthma to our community.